Problem solving in clinical practice: the sick infant with low sodium and high potassium. Issue 1 (21st February 2020) - Tse, Yincent; Singhal, Nidhi; McDonald, Leigh; Gopal, Milan; Lall, Anupam; Johnstone, Helen; Cheetham, Timothy
Abstract : Many paediatricians will be faced with a sick infant who on investigation is found to have hyponatraemia and hyperkalaemia at some time in their career. The focus of initial management includes the treatment of potentially life-threatening hyperkalaemia with concurrent investigation aiming to elucidate whether the underlying cause reflects a primarily renal or endocrine pathology. We describe the presentation of two infants who each presented with one of the more common underlying diagnoses that led to this biochemical disturbance and discuss the approach to immediate treatment, diagnostic work-up and longer term management.